Striking parallels between carotid body glomus cell and adrenal chromaffin cell development - Hockman, D; Adameyko, I; Kaucka, M; Barraud, P; Otani, T; Hunt, A; Hartwig, A; Sock, E; Waithe, D; Franck, M; Ernfors, P; Ehinger, S; et al. (Elsevier, 2018)
Carotid body glomus cells mediate essential reflex responses to arterial blood hypoxia. They are dopaminergic and secrete growth factors that support dopaminergic neurons, making the carotid body a potential source of patient-specific cells for Parkinson's disease therapy. Like adrenal chromaffin cells, which are also hypoxia-sensitive, glomus cells are neural crest-derived and require the transcription factors Ascl1 and Phox2b; otherwise, their development is little understood at the molecular level. Here, analysis in chicken and mouse reveals further striking molecular parallels, though also some differences, between glomus and adrenal chromaffin cell development. Moreover, histology has long suggested that glomus cell precursors are ‘émigrés’ from neighbouring ganglia/nerves, while multipotent nerve-associated glial cells are now known to make a significant contribution to the adrenal chromaffin cell population in the mouse. We present conditional genetic lineage-tracing data from mice supporting the hypothesis that progenitors expressing the glial marker proteolipid protein 1, presumably located in adjacent ganglia/nerves, also contribute to glomus cells. Finally, we resolve a paradox for the ‘émigré’ hypothesis in the chicken - where the nearest ganglion to the carotid body is the nodose, in which the satellite glia are neural crest-derived, but the neurons are almost entirely placode-derived - by fate-mapping putative nodose neuronal 'émigrés' to the neural crest.